Partial Orbicularis Resection for the Augmentation of Traditional Internal Brow Pexy: The "Tuck and Rise". Issue 6 (November 2016) - Armstrong, Blair K.; Sobti, Deepak; Mancini, Ronald
Abstract : Purpose: Brow ptosis commonly occurs with aging. Minimally invasive techniques are varied and include neurotoxin paralysis of eyebrow depressors and internal brow pexy. The authors present a modification of the traditional brow-pexy surgery which incorporates weakening of the lateral eyebrow depressor, the orbicularis oculi muscle, to synergistically influence brow position. Methods: This retrospective review includes 44 brows in 22 patients treated over a 14-month period. All patients underwent surgery by a single surgeon (RM) at UT Southwestern Medical Center. The surgical technique includes partial orbicularis resection to augment the traditional internal brow pexy. Preoperative and postoperative photographs were analyzed using ImageJ software. Results: This procedure has been successfully performed on 44 brows in 22 patients with no complications and a high satisfaction rate. ImageJ analysis demonstrates an average elevation of 2.42 mm of the lateral tail of the brow with improved brow contour, volume, and symmetry. Conclusions: The "Tuck and Rise" has proven a simple, minimally invasive, and effective technique to volumize and elevate the lateral tail of the eyebrow. Abstract : Partial resection of the orbicularis oculi, the only natural depressor of the lateral eyebrow, can augment traditional internal brow-pexy in restoring elevation, volume, and symmetry to the tail of the eyebrow.Supplemental Digital Content is available in the text.